極域における雲の下向き長波放射フラックスへの寄与 - 山田, 恭平; 早坂, 忠裕; 岩渕, 裕信; Kyohei, Yamada; Tadahiro, Hayasaka; Hironobu, Iwabuchi (2013)
Downward longwave flux is an important factor to determine surface radiation budget, water cycle, and climate change. Cloud is a dominant factor to absorb and emit longwave flux, however the understanding of cloud effect is limited. In polar regions, the contribution of cloud is especially important because of small amount of water vapor. The present study evaluated cloud radiative effect at 4 diffent sites in polar regions, which belong to Baseline Surface Radiation Network (BSRN), with radiosonde and radiation observations. The cloud radiative forcing (CRF) is defined by the difference between calculated downward longwave radiation assumed clear-sky (DLRCalClear) and observed radiation under all-sky (DLRObsAll). Calculation is executed with mstrnX, 1-dimentional two stream scheme. Under clear-sky condition, DLRObsAll and DLRCalClear showed good correlation, DLRObsAll – DLRCalClear = −0.79±5.06W/m2 and correlation coefficient is 0.992. CRF increases with an increase in diffusion ratio, which is the index of cloud amount defined with the ratio of observed diffuse shortwave radiation to total shortwave radiation. CRF varies from about −10 W/m2 to 110 W/m2. The absolute values of forcing are not so different among four sites, however the relative values are different. South pole, where the monthly average of precipitable water is less than 2mm, shows clearly smaller relative contribution than the other sites. Under dry and cold climate conditions, CRF varies widely and the strong negative value emerged. The negative value appeared frequently when temperature inversion layer exists at low altitude. CRF shows smaller tendency when temperature inversion exists at near surface than no temperature inversion days. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月14日（木） 統計数理研究所 ３階セミナー室１（D305） conference object